The Participation Patterns of Youth with Down Syndrome - MacDonald, Megan; Leichtman, Jennifer; Esposito, Phil; Cook, Nicole; Ulrich, Dale Allen (Frontiers in Public Health, 2016)
Purpose: The purpose of this paper was to investigate the participation patterns of children with Down syndrome (DS) using the construct of participation as defined by the International Classification of Functioning Disability and Health (ICF). Method: Sixty-two children with DS were recruited between the ages of 9- 17 years. All participants were given an interview-administered version of the Children's Assessment of Participation and Enjoyment (CAPE) to measure participation.38 Results: Children with DS participated the most often, based on frequency, in recreational activities (p < 0.001); social activity-types represented the greatest extension into the community based on with whom the children participated with (p < 0.05); finally, physical and social activities represented the greatest extension into the community geographically (p < 0.001). In addition, children with DS are significantly more active in activities that are informal in nature. Conclusions: Children with DS participate in a number of activities however, the extent of their participation within these activities differs depending on the participation pattern examined. Implications for educational and community-based programs are discussed.